A Narrative Approach to the Standard of Originality in EU Copyright Law: The Story of a Dress - Härkönen, Heidi (Springer Nature, 2025)
“Originality” is the key requirement for copyright protection in the EU. Judgements of the Court of Justice of the European Union (CJEU) such as Painer and Brompton show that many aspects of the standard of originality are linked as much to the creative process as to the resulting subject matter. This is particularly true for the “free and creative choices” that authors must make when producing a copyright-protected work. However, we do not have much information about how the standard of originality is manifested in the practices of the creative sectors, especially when it comes to applied arts and industrial design, such as fashion design. Combining a narrative approach to research with the doctrinal study of law, this article examines a creative process by following the journey of the design of a garment – a dress – from idea to expression. The narrative is used as a case study to illustrate the kinds of choices made in the creative process that are significant for the dress to merit copyright protection. The significance of these copyright-relevant choices is contrasted with EU design law where they may lead to a different protection outcome. It is concluded that the more information we have about the creative process of an artistic work – regardless of category – the more accurately we can assess whether it qualifies for copyright protection. The article further argues that the process of fashion design is not inherently any less creative than other, less controversial, areas of copyright protection.